2021
DOI: 10.1111/ene.15125
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐eclampsia, gestational diabetes and hypertensive disorders in patients with intracranial aneurysms: A case–control study

Abstract: Background and purpose:The aim of this study was to define the prevalence of preeclampsia, gestational hypertension (HT), chronic HT, and gestational diabetes during pregnancy in a defined population of patients with saccular intracranial aneurysms (sIAs). Methods:We included all patients with sIA, first admitted to the Neurosurgery Department of Kuopio University Hospital from its defined catchment population between 1990 and 2015, who had given birth for the first time in 1990 or later. The patients' medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…Candidate predictors were prespecified based on literature: age at screening, female sex, type of kinship with index being siblings, smoking, excessive alcohol consumption, hypertension, hyperlipidemia, diabetes, hypertensive pregnancy complication, regular physical exercise, the interaction between female sex/smoking, and smoking/excessive alcohol consumption. 7,[20][21][22][23][24] The number of affected relatives was not included as a candidate predictor because all FDRs had only 1 FDR with UIA(s) (the index patient) during inclusion. 22 All candidate predictors were included in the full model, regardless of their association in the univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Candidate predictors were prespecified based on literature: age at screening, female sex, type of kinship with index being siblings, smoking, excessive alcohol consumption, hypertension, hyperlipidemia, diabetes, hypertensive pregnancy complication, regular physical exercise, the interaction between female sex/smoking, and smoking/excessive alcohol consumption. 7,[20][21][22][23][24] The number of affected relatives was not included as a candidate predictor because all FDRs had only 1 FDR with UIA(s) (the index patient) during inclusion. 22 All candidate predictors were included in the full model, regardless of their association in the univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A possible connection between familial sIA disease and familial pre‐eclampsia has not been reported. In our previous study, pre‐eclampsia was more common in sIA patients than in their matched controls and sIA patients with pre‐eclampsia had more frequently irregularly‐shaped aneurysms [23]. The current study was conducted to verify the connection between pre‐eclampsia and sIA disease in an extended study population.…”
Section: Introductionmentioning
confidence: 92%
“…Six sIA family trees were illustrated with the timelines of two or three generations since the birth on a linear calendar year axis (1920-2020) [50]. In Kotikoski et al (2021), the linear age timelines of 22 female sIA patients indicated when pre-eclampsia was diagnosed in relation to the diagnosis of unruptured sIA, aSAH, and hypertension [48].…”
Section: Construction and Optimization Of The Individual Timeline Panelsmentioning
confidence: 99%